Biostimulant Effect on the Growth and Production of Shallot in Peatlands - Azri Azri (Agros Journal of Agriculture Science, 2017)
Biostimulant from seaweed extract contains nutrients, amino acids, cytokines, auksin, laminaran, fukoidan, alginat and betain which stimulate plant metabolism so as to increase growth and yield of plants. Some research results indicate that spraying biostimulant from seaweed in corn plant can increase shoots weight of 37 until 42 percent and root weight of 34 up to 45 percent. In this study biostimulan used enriched with elements S, Zn, Cu and Mn to meet the needs of onion plants. Research using Randomized Block Design  consists of two factors that is seaweed and red onion varieties with five replication. Research treatment are: without giving of seaweed and giving of seaweed whereas shallot varieties used are Bima, Moujung, and Sumenep. Results showed that giving seaweed improved peatland fertility and increased shallot production. Biostimulant and real varieties increase the growth and production of shallots. Value of profit and value B/C ratio 2.37; 1.99 dan 1.11, then the utilization of biostimulant to increase the productivity of onion in peat land, onion cultivation of Bima and Moujung varieties is economically feasible to be applied by peatland farmers in West Kalimantan. Key-words: Biostimulant, shallot, peatland